Corporeal identification in selected works by Berni Searle - Taggart, Emma (Rhodes University, Faculty of Humanities, Department of Fine Art, 2008)
Through a detailed analysis of a selection of works produced between 1999 and 2003 by the South African artist Berni Searle, this thesis explores the need to theorise a corporeal viewer in the process of interpreting art works. Such an approach is particularly necessary when dealing with an artist such as Searle because her work, which deals predominantly with the theme of identity, appeals not only to conceptual but also to experiential and corporeal understandings of identity. Searle incorporates the viewer into an experience of her own identity through a physical identification that the viewer feels in relation to her work. For viewers this means that they are made aware of how their own identity in the moment of interpretation is contingent on visual, mental and physical components. In order to develop this argument the work of psychoanalyst Jacques Lacan and the phenomenologist Maurice Merleau-Ponty is drawn on. These two theorists are very useful for an argument of this nature because both interpret identity as a construction involving an enfolding between the mind and, via the act of vision, the body of the subject. Through an inclusion of the corporeal element in interpretation, this thesis also offers a critique of interpretive theories that would reduce analysis to an interaction between eye and mind by analyzing how the viewer's body participates in the act of looking.
Keywords: Searle, Berni; Lacan, Jacques, 1901-1981 -- Criticism and interpretation; Merleau-Ponty, Maurice, 1908-1961 -- Criticism and interpretation; Women artists -- South Africa; Body art -- South Africa; Self-portraits